Problem based learning and design thinking methodologies for teaching renewable energy in engineering programs: Implementation in a Colombian university context. Issue 1 (31st December 2023) - Colmenares-Quintero, Ramón Fernando; Caicedo-Concha, Diana Milena; Rojas, Natalia; Stansfield, Kim E.; Colmenares-Quintero, Juan Carlos
Abstract: The rapid depletion of fossil fuel reserves, population growth, and increasing environmental pollution have forced a change in the search for alternatives to produce and use energy. Currently, renewable energies (RE) have achieved more efficient advances to produce energy from non-conventional and inexhaustible sources, which can meet the basic needs of society and whose environmental impact is a door of opportunities for all. For this reason, academia has a preponderant role in ensuring that engineers are fully equipped with the necessary skills to provide feasible and contextualised solutions for this era of energy transition framed by the UN Sustainable Development Goals (SDGs). This article explores the impact on the development of the necessary skills for engineers in the renewable energy sector by tracing a route towards the acquisition of renewable energy knowledge with strategically organised work teams of undergraduate students, where two methodologies that are gaining ground in engineering education programs are applied: Problem Based Learning(PBL)and Design thinking (DT).After the validation of these techniques, it is concluded that bringing engineering students closer to real contexts related to renewable energies and above all with an objective of impact on communities, it is the right way to build knowledge in teams, in an immersive and committed way with the institution, which has developed and implemented an innovative pedagogical method based on the application of a critical educational model focused on the development of competencies, where the union of new technologies with the teaching processes on which this research is based is envisioned for the future.